Prerequisites of syntactic-semantic markings - Abdikarim , Н. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2023)
The article discusses the issue of the need to create and officially approve a list of conventional signs (marks) of morphological glossing on the basis of the international Leipzig rule for further improvement of the Kazakh language corpora, developed in connection with the country's digitalization policy, and its use in linguistic research, educational process and other purposes. The analysis of meta tags used in the corpora of the Kazakh language and in the field of domestic computational linguistics has been carried out. At the same time, attention is also paid to the work of related languages in this direction and it is shown that the conventional signs and symbols in them have common features or features that are unique to this language. According to the author, the conventional signs used in morphological glossing are the basis for creating a corpus of the Kazakh language, equipped with syntactic-semantic markup. Also, such conventional signs provide new opportunities for comparative or comparative study of the native language with other languages as a reference language, for the presentation of language materials in a concise and visual form, for the description and processing of text data on a computer; and new opportunities for conducting modern linguistic research using IT technologies and developed corpora.